Long-term aneurysm recurrence and de novo aneurysm formation after surgical treatment of unruptured intracranial aneurysms: a cohort study and systematic review. (2nd April 2020) - Fingerlin, Tamara J.; Rychen, Jonathan; Roethlisberger, Michel; Taub, Ethan; Mariani, Luigi; Guzman, Raphael; Zumofen, Daniel W.
ABSTRACT: Objective : There is a relative lack of literature on long-term aneurysm recurrence and de novo aneurysm formation following surgical treatment of unruptured intracranial aneurysms. This retrospective single-center cohort study, therefore, analyzes the incidence of aneurysm recurrence, and the incidence of de novo aneurysms formation in patients with at least 10yrs of radiological follow-up. The data are put into the context of a systematic review of the literature. Methods : Patients that underwent surgical treatment of an unruptured intracranial aneurysm at the Basel University Hospital were retrospectively identified. The rate of recurrent or de novo aneurysm formation was assessed for all patients with imaging follow-up ≥10yrs. A systematic review including studies with a mean follow-up period of ≥10yrs was then performed. Results : A total of 95 patients had undergone surgical treatment of an unruptured intracranial aneurysm between 1994 and 2008. Twenty-one patients (22.1%) had available imaging follow-up ≥10yrs (mean: 13.1yrs). In these patients, aneurysm recurrence and de novo aneurysm formation were equally found in 23.8% (n = 5; 1.8%/yr). There was no case of aneurysm rupture from a recurrent or a de novo aneurysm. The systematic literature review covered a combined cohort of 1778 patients over a mean follow-up period of 14.0yrs. In this cohort, the aneurysm recurrence rate was 16.4% (0.7%/yr), and the rate of de novo aneurysm formation was 6.2% (0.4%/yr). Discussion : Despite some discrepancy regarding the incidence, both cohorts show a non-negligible long-term risk of aneurysm recurrence and de novo aneurysm formation, which warrants life-long imaging follow-up. Abbreviations: SD: standard deviation; DSA: digital subtraction angiography; CTA: computed tomography angiography; MRA: magnetic resonance angiography; MCA: middle cerebral artery; ACA: anterior cerebral artery; ACommA: anterior communicating artery; ICA: internal carotid artery; ADPKD: autosomal dominant polycystic kidney disease; MeSH: Medical Subject Headings